On the Solvability of the Same Nonlinear Compound Boundary Valued Problems (Journal of Partial Differential Equations, 1994)
In this paper, we may make tbe following: {|W(t)| = &#934(t), \qquad t &#8712 L &#8834 &#8706D Re[a(t) - i · b(t)]W(t) = &#968(t), t &#8712 M = &#8706D - L equal to searching for a positive solution of nonlinear singular integral equation. The solvability and discrete approximate solution of the singular integral equation have been studied.
Keywords: Analytic function; nonlinear boundary valued problem; nonlinear singular integral equation